2022
DOI: 10.1038/s41541-021-00421-5
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination with Bacille Calmette-Guérin (BCG) is associated with an increased risk of abscess and lymphadenopathy

Abstract: The reported frequency and types of adverse events following initial vaccination and revaccination with Bacille Calmette-Guérin (BCG) varies worldwide. Using active surveillance in a randomised controlled trial of BCG vaccination (the BRACE trial), we determined the incidence and risk factors for the development of BCG injection site abscess and regional lymphadenopathy. Injection site abscess occurred in 3% of 1387 BCG-vaccinated participants; the majority (34/41, 83%) resolved without treatment. The rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…The higher likelihood of BCG scarring in participants with prior BCG vaccination history may relate to an underlying immunological boosting phenomenon, as BCG revaccination has been associated with more pronounced local injection site reactions [ 34 ], larger scar size [ 35 ] and enhanced protective effects (against respiratory tract infections) in studies in adolescents [ 36 ] and adults [ 37 ]. BCG injection site reactions (presence and size) have been shown to correlate with the magnitude of the mycobacteria-specific T-cell immune responses [ 10 ] as well as specific and heterologous cytokine responses [ 9 ] in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The higher likelihood of BCG scarring in participants with prior BCG vaccination history may relate to an underlying immunological boosting phenomenon, as BCG revaccination has been associated with more pronounced local injection site reactions [ 34 ], larger scar size [ 35 ] and enhanced protective effects (against respiratory tract infections) in studies in adolescents [ 36 ] and adults [ 37 ]. BCG injection site reactions (presence and size) have been shown to correlate with the magnitude of the mycobacteria-specific T-cell immune responses [ 10 ] as well as specific and heterologous cytokine responses [ 9 ] in vitro .…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 17 To consider BCG revaccination, we must acknowledge that the rate of adverse events (AE) also varies globally. While BCG vaccine batch variability was found by Soh and colleagues (2014) to affect the occurrence of AEs, 18 Villanueva et al 19 did not find any association between the BCG vaccine batch and AEs. There is thus a paucity of evidence comparing the effectiveness and safety of different BCG batches.…”
mentioning
confidence: 82%
“… 3 This finding is recalled in this issue (see below). Villanueva et al 19 reported an increased risk of injection site abscess and lymphadenopathy following BCG revaccination in Australian health care workers (HCW) during the influenza vaccination campaign.…”
mentioning
confidence: 99%
“…Questions addressed the presence, time to onset, duration, and severity of pain, erythema, swelling and tenderness at the vaccination site. Information on BCG vaccination site reaction was collected in a similar way, and has been published elsewhere [ 16 ].…”
Section: Methodsmentioning
confidence: 99%